Thinking Twice about the Cervical Mass: A Case Report of Primary Vaginal Leiomyosarcoma and Review of the Literature - Caroline C. Davitt; Yingao Zhang; Anthony B. Costales (Hindawi Limited, 2024)
Primary vaginal leiomyosarcoma (LMS) is an unusual cause of aggressive gynecologic cancer which requires prompt surgical treatment for favorable outcomes. Definitive diagnosis and treatment render unique challenges to clinicians based on vague presentation and limited evidence for management. Here, we describe a case of vaginal LMS in a middle-aged woman with a history of cervical dysplasia found to have a proximal vaginal mass after presenting with vaginal discharge and cramping pain. The patient was diagnosed on pathologic surgical specimen and subsequently underwent definitive surgical treatment. She remains with no evidence of disease 20 months later. In our report, we emphasize the nuances of surgical management including localized source control in those desiring future fertility. Ultimately, we make recommendations for surgical treatment and surveillance based on the available published literature.